Implementasi Project-Based Learning Berbantuan Simurelay Pada Mata Pelajaran Instalasi Motor Listrik - Alfi Fahrezi; Oriza Candra (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2026)
This study investigated the effect of implementing the Project-Based Learning (PjBL) model supported by the Simurelay application on students’ learning outcomes in the Electrical Motor Installation subject. The study employed a one-group pretest–posttest design involving 26 Grade XI students from the Electrical Power Installation Engineering program at SMKN 1 Bonjol. Data were collected through cognitive tests and skills observations. The results showed a substantial increase in students’ average scores, from 54.62 on the pretest to 82.00 on the posttest. An N-gain score of 0.56 confirmed that the improvement was in the moderate category. Regarding learning mastery, there was a marked increase, with 88% of the students meeting the Learning Objective Achievement Criteria after the intervention, whereas nearly all students had failed to meet the criteria before the intervention. In addition to cognitive improvement, students demonstrated good psychomotor skills in designing and simulating electrical circuits. In conclusion, the combination of PjBL and Simurelay was effective in improving students’ theoretical understanding and practical skills, while also fostering independence and collaboration in completing electrical motor installation projects.